Fostering Tolerance and Unity in Diverse Communities through Mosque-Community Relations - Wibowo, Aqiilah Nur Aini; Sufyanto, Sufyanto (Indonesian Journal of Islamic Studies, 2024)
This study investigates tolerance communication between the management of Al-Furqaan mosque and the residents of Jenggot Village, a diverse community in Sidoarjo Regency. Despite varying races, ethnicities, and beliefs, the village maintains an environment of tolerance and mutual respect. The research aims to understand how this communication is established and maintained. Employing descriptive qualitative methods, including observation and documentation, the study finds that mosque management actively participates in community events and contributes to fulfilling their needs as a form of tolerance. These efforts foster unity and mutual respect among residents. This research highlights the importance of religious institutions in promoting tolerance in diverse communities, offering valuable insights for policymakers and community leaders. Highlight: Active mosque participation fosters community unity and tolerance. Residents show mutual respect for diverse beliefs and opinions. Qualitative study explores mosque's role in fostering community tolerance. Keywords: Tolerance Communication, Mosque Management, Diverse Community, Mutual Respect, Qualitative Research.